Maritime surveillance in Cyprus using Sentinel - 1 SAR - Kalogirou, Eleftheria; Melillos, George; Hadjimitsis, Diofantos G.; Schwarz, Egbert; Wiehle, Stefan (My University, 2023)
Maritime surveillance plays a critical role in ensuring the safety and effective management of maritime activities. This study focuses on the use of Sentinel-1 Synthetic Aperture Radar (SAR) data for marine surveillance in Cyprus which offers all-weather imaging capabilities and enables monitoring of marine activities such as vessels detection, oil spill detection and wind speed direction. Also, the study includes the import and pre-processing of SAR data in the SNAP (Sentinel Application Platform) software as well as the application of advanced algorithms and techniques where vessels detection, oil spill detection on the water surface and wind speed and direction can be derived. Therefore, the results of this research have significant implications for maritime safety assessment, environmental protection and resource management in Cyprus. The use of Sentinel-1 SAR data for maritime surveillance in Cyprus enhances the island-wide surveillance capability to detect potential threats and to respond immediately.
Keywords: Maritime safety; Oil spills; SAR; Sentinel-1; Vessels Detection; Wind Speed Direction